Doing it Differently. Link and Learn — the work of the Indigenous Education and Training Alliance - Taylor, Pauline (The Australian Journal of Indigenous Education, 2002)
The Indigenous Education and Training Alliance(IETA) is a staff college of Education Queensland. Its primary focus is to broker and deliver professional development to educators around the policies contained within Partners for Success: strategy for the continuous improvement of education and employment outcomes for Aboriginal and Torres Strait Islander Peoples in Education Queensland(Education Queensland, 2000b). This paper describes how IETA's work to support one of the policies, Literacy for Aboriginal and Torres Strait Islander Students, has been theorised and enacted. It also discusses the organisation's successes and challenges in the significant area of language and literacy pedagogy for Indigenous students.